Research on positioning precision testing methods in GPS continuously operating reference station system - TANG Wei-ming1; LOU Yi-dong1; LIU Hui1; CHEN Ri-gao2; YANG Qiu2 (Tongxin xuebao)
The positioning Precision testing methods of CORS were introduced in detail.Based on the testing method of static fixed point and the method of comparing with the post-processing positioning result,the paper put forward land regular geometrical track kinematic testing method and fixed baseline length relative testing method.The testing resulted of a CORS system obtained with the former three methods show that the proposed method are valid and fit to the general precision testing of most CORS system.